(untitled) (Universal International Scientific Journal, 2026)
In our rapidly developing world, the changes taking place do not leave every citizen indifferent, especially the creation of more and more conditions for women and girls. Also, this article extensively highlights the fact that increasing the role of women and girls in state administration of our country, further strengthening their social protection system, strengthening their health, creating the necessary conditions for girls to receive education, educating talented and educated girls and increasing their scientific potential remain one of the important issues of today, and comprehensive work is being carried out in the areas of comprehensive assistance in their acquisition of education and professional skills, as well as ensuring employment, and further supporting entrepreneurial initiatives.